2003
DOI: 10.1161/01.str.0000067703.71251.b6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Stroke in the Hunter Region, Australia

Abstract: Background and Purpose-Seasonal variation in stroke has long been recognized. To date, there are minimal published data on seasonal variations in rates of stroke and subsequent case fatality in the Southern Hemisphere. The aim of this study was to examine stroke seasonality through the use of data from a hospital-based stroke register in the Hunter Region of New South Wales, Australia. Methods-From July 1, 1995, to June 30, 2000, 3803 stroke events were registered in residents of the Hunter Region, New South W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
92
2
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 46 publications
11
92
2
12
Order By: Relevance
“…An earlier study from Japan reported that diurnal temperature change may affect daily blood pressure or autonomic nervous system balance, and, if a considerable diurnal temperature change induces considerable hemodynamic change, it may trigger cerebral stroke. 31 In addition, some studies reported stronger seasonality in stroke in older age groups than in younger ones, 10,11,32,33 as seen in our study. We found a September preponderance in the monthly incidence of AS and IS.…”
Section: 23-25supporting
confidence: 83%
See 1 more Smart Citation
“…An earlier study from Japan reported that diurnal temperature change may affect daily blood pressure or autonomic nervous system balance, and, if a considerable diurnal temperature change induces considerable hemodynamic change, it may trigger cerebral stroke. 31 In addition, some studies reported stronger seasonality in stroke in older age groups than in younger ones, 10,11,32,33 as seen in our study. We found a September preponderance in the monthly incidence of AS and IS.…”
Section: 23-25supporting
confidence: 83%
“…Most studies have demonstrated that the incidence of stroke increases in the winter and spring and decreases in the summer and autumn. [3][4][5][6][7][8][9][10][11] However, some studies have reported increases in the incidence of stroke in response to dramatic temperature changes in the spring and autumn, [12][13][14] whereas in other studies, no seasonal variation has been demonstrated. [15][16][17] Because most previous studies have addressed large regions with varying climate, studies on smaller regions with similar weather and environments could provide important information on this topic.…”
mentioning
confidence: 99%
“…As mentioned before, different patterns of incidence were reported for each geographical region in different studies. In some studies, no significant relationship was observed between the incidence of stroke and season of the year (24,25), but in some countries, winter (29,30) or summer (21,31,32) were introduced as the risk factor for stroke. However, a study in New Zealand found that strokes were less likely to occur during the summer and autumn than in the winter or spring (33).…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistical information in Italy, the incidence of stroke is lower during the summer and is higher in the fall than in the winter (20). But, in some regions of Australia, more stroke rate is reported in the summer than in the winter (21). In Finland, the rate of cerebral-vascular attacks in men is higher on Mondays than on Sundays (22) and also another study revealed that the peak of vascular attacks is in the early hours of the morning, and then the attacks' rate reduces in the rest hours of the day (23).…”
Section: Introductionmentioning
confidence: 99%
“…Palavras-chave: acidente vascular cerebral, temperatura, risco cardiovascular, sazonal. The correlation between strokes and seasonal variations have been studied in various places [1][2][3][4][5][6][7][8] . Some studies around the world have reported an increase of incidence, mortality, and stroke hospitalization during the coldest months of winter.…”
mentioning
confidence: 99%